2003
DOI: 10.2337/diacare.26.3.764
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Insulin Using the AERx Insulin Diabetes Management System in Healthy and Asthmatic Subjects

Abstract: , Hayward, CA) delivers an aerosol of liquid human insulin to the deep lung for systemic absorption. This study examined the effects on pulmonary function, pharmacokinetics, and pharmacodynamics of inhaled insulin in asthmatic and nonasthmatic subjects without diabetes. RESEARCH DESIGN AND METHODS-A total of 28 healthy and 17 asthmatic (forced expiratory volume during the first second [FEV 1 ] 50 -80% of predicted value) subjects were enrolled in a two-part, open-label trial. To assess insulin pharmacokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(55 citation statements)
references
References 28 publications
0
50
0
5
Order By: Relevance
“…A study in healthy volunteers suggested that changes in the inhaled volume and depth of inspiration influenced pharmacokinetics of insulin delivered using this system (44). Upper respiratory tract infections do not seem to induce any clinically relevant changes in pharmacokinetics or pharmacodynamics (although t max is significantly reduced) (46), whereas the dose may need to be adjusted upward in asthmatics (47).…”
Section: Aerxmentioning
confidence: 99%
“…A study in healthy volunteers suggested that changes in the inhaled volume and depth of inspiration influenced pharmacokinetics of insulin delivered using this system (44). Upper respiratory tract infections do not seem to induce any clinically relevant changes in pharmacokinetics or pharmacodynamics (although t max is significantly reduced) (46), whereas the dose may need to be adjusted upward in asthmatics (47).…”
Section: Aerxmentioning
confidence: 99%
“…Limited information has been published regarding the impact of asthma on inhaled insulin pharmacokinetic and/or glucodynamic parameters. Henry et al (16), using an aerosol of aqueous insulin, reported significantly reduced insulin exposure and reduced glucose effects in mild-tomoderate asthmatic subjects compared with a healthy group. In our study, mild and moderate asthma groups had similar reductions in inhaled insulin exposure, though differing glucose effects, relative to healthy subjects.…”
Section: Conclusion -Results From Thismentioning
confidence: 99%
“…Nos estudos iniciais, diabéticos asmáticos absorveram menos insulina por via inalatória, necessitando de doses maiores do que diabéticos sem asma para obterem controle da glicemia (57).…”
Section: Implicações Clínicasunclassified